The Foregoing And Delaying Phenomenon In The Andalusian Muwashshahat - Faris, Isah; Albahlool, Ammar (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The research studies purposes of The Foregoing And Delaying Eloquently in the Andalusian Muwashshahat, because it was known that this Type –That was described one of many types of meanings science in the eloquent – does a lot of purposes such as: showing touching, showing happiness in hurry … etc., This type was spread in the Andalusian Muwashshahat, and it was used a lot by poets of Andalusian Muwashshahat in the Andalusian age, although there were differences in purposes of poetry in these Muwashshahat . This research will deal with these many purposes eloquently for this eloquent type in the Andalusian Muwashshahat, Explaining the details by citing poetry syllable for each purpose, that elaborates deeply the eloquent purpose by analyzing study bases on frame of the Foregoing And Delaying, its building, its effect, its doing, and its Denotation value.